2003
DOI: 10.1007/s11664-003-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon structural transitions and ohmic contacts on 4H-SiC

Abstract: The structural properties of sputtered carbon films on SiC are investigated using X-ray photoelectron spectroscopy (XPS) and Raman scattering. The asdeposited films are amorphous with an sp 2 /sp 3 ratio of 1. The sp 2 carbon structures gradually increase with increasing temperatures and consist of amorphous aromatic-like carbon, polyene-like carbon, and nano-size graphite flakes. Schottky contacts on carbon/SiC are converted to ohmic contacts after annealing. The concentration of nano-graphitic flakes relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The reaction zone is observed to grow with increasing annealing temperature. The Ru/4H-SiC interface of the as-deposited sample as depicted in Fig [ 6,7,8,9,10,11] . The intensity ratio of the D and G peaks can be used to approximate the size of the crystalline graphite or degree of disorder of the graphite that is formed [6].…”
Section: Ruthenium Reaction With and Diffusion In 4h-sic And 6h-sic Umentioning
confidence: 99%
“…The reaction zone is observed to grow with increasing annealing temperature. The Ru/4H-SiC interface of the as-deposited sample as depicted in Fig [ 6,7,8,9,10,11] . The intensity ratio of the D and G peaks can be used to approximate the size of the crystalline graphite or degree of disorder of the graphite that is formed [6].…”
Section: Ruthenium Reaction With and Diffusion In 4h-sic And 6h-sic Umentioning
confidence: 99%
“…Ru is observed to react with 6H-SiC, and is found at 2300 x 10 15 at./cm 2 from the surface (Fig.6) after annealing at 1000 o C. Raman analysis of the thin film sample (Fig. 7) shows the formation of graphite as indicated by a typical carbon D peak at 1354 cm -1 and G peak at 1589 cm -1 [12,13,14,15,16,17] . The intensity ratio of the D and G peak are used to approximate the size of the crystalline graphite or degree of disorder of the graphite .…”
Section: Resultsmentioning
confidence: 96%
“…This finding is supported by Seyller et al [30] who in their studies found that the formation of graphite at the metal-SiC interface may lead to ohmic contact formation as the SBH of graphite on n-type 6H-SiC is very small (about 0.3 eV) . Lu et al [13] also found out that the carbon contact on SiC exhibited schottky and ohmic contact behaviour in the annealing temperature range of 900-1350 o C. They found that the temperature of transition from schottky to ohmic contact in Carbon/SiC structure depends on the doping concentration of SiC and amount of nano-graphitic flakes formed. *CV curve is not a straight line.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations